The selection eaudiobook - Cass, Kiera (The Selection, 2012)
Fall in love—from the very beginning. Discover the first book in the captivating, #1 New York Times bestselling Selection series. Prepare to be swept into a world of breathless fairy-tale romance, swoonworthy characters, glittering gowns, and fierce intrigue perfect for readers who loved Divergent, Delirium, or The Wrath & the Dawn. For thirty-five girls, the Selection is the chance of a lifetime. The opportunity to escape a rigid caste system, live in a palace, and compete for the heart of gorgeous Prince Maxon. But for America Singer, being Selected is a nightmare. It means turning her back on her secret love with Aspen, who is a caste below her, and competing for a crown she doesn't want. Then America meets Prince Maxon—and realizes that the life she's always dreamed of may not compare to a future she never imagined. Don't miss The Betrothed, a glittering royal romance sure to captivate Kiera Cass's legion of loyal readers and lovers of courtly intrigue alike!